Pengaruh Profitabilitas, Leverage, dan Kepemilikan Manajerial terhadap Kebijakan Dividen dengan Likuiditas sebagai Variabel Moderasi - Cahyono, Gilang Indra; Asandimitra, Nadia (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The purpose of this study is to determine whether liquidity can be a moderating variable between the effect of profitability, leverage, and managerial ownership on dividend policy. The sample of this study consisted of 42 companies confirmed by the Indonesia Stock Exchange in property, real estate and building construction. The sampling technique used a census sample. The analysis technique uses Multiple Regression Analysis (MRA). The findings obtained are that there is no influence between profitability on dividend policy than dividend policy is influenced by leverage and managerial ownership. The relationship between profitability and managerial ownership on dividend policy fails to be moderated by liquidity. While liquidity Intervening variables strengthen the effect of profitability on dividend policy can be added to future research to account for variations in research results.